2007
DOI: 10.1007/s11262-007-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunogenicity of minor envelope protein GP3 of porcine reproductive and respiratory syndrome virus in mice

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most economically significant viral diseases in swine industry. Though the minor envelope protein GP3 is associated with protective immunity, its immunogenicity and protective mechanism are poorly known. In this study, two recombinant adenoviruses, rAd-GP3 expressing complete GP3 and rAd-tGP3 expressing truncated GP3 in which aa2-64 were deleted, were constructed and the immunogenicity were tested in a mouse model. Four groups of BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The 254-AA GP3 protein is encoded by ORF3 and has a molecular mass of approximately 42 kDa [33, 34]. The GP3 protein is one of the most variable structural proteins among the PRRSVs, with only 54% to 60% AA sequence identity shared between the Type-1 and Type-2 strains [24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…The 254-AA GP3 protein is encoded by ORF3 and has a molecular mass of approximately 42 kDa [33, 34]. The GP3 protein is one of the most variable structural proteins among the PRRSVs, with only 54% to 60% AA sequence identity shared between the Type-1 and Type-2 strains [24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…After mice immunized with the recombinants rAd-GP3 and rAD-tGP3, PRRSV-specific neutralization antibodies, T-cell proliferation responses and cytotoxic T responses were observed, although the production of neutralizing antibodies was tardy. Interestingly, the immune response elicited by rAd-tGP3 was stronger than that of rAd-GP3 (Jiang et al, 2007). The mechanism underlying this phenomenon remains unclear, but it might suggest some adverse factors lie within the deleted sequence of GP3.…”
Section: Recombinant Vectors Expressing Porcine Reproductive and Respmentioning
confidence: 96%
“…The authors also found that ORF7 gene product (N protein) is the most immunogenic protein of PRRSV, but the antibodies induced in sows are non-protective and may even interfere with protection (Plana Duran et al, 1997). The immunogenicity of GP3 was further characterized by using two recombinant adenoviruses (rAd), rAd-GP3 expressing complete GP3 and rAD-tGP3 expressing truncated GP3 in which amino acids 2-64 were deleted (Jiang et al, 2007). After mice immunized with the recombinants rAd-GP3 and rAD-tGP3, PRRSV-specific neutralization antibodies, T-cell proliferation responses and cytotoxic T responses were observed, although the production of neutralizing antibodies was tardy.…”
Section: Recombinant Vectors Expressing Porcine Reproductive and Respmentioning
confidence: 99%
“…Most of these strategies rely on the use of DNA-based vaccines [21-26], transgenic plants [27,28], bacterial vectors [29-31], or viral vectors. Among the viral vectors used are non-replicative human [17,32-39] and canine adenoviruses [40], transmissible gastroenteritis virus [41], the modified strain of vaccinia virus [16], pseudorabies virus [15,42] and fowlpox virus [43]. Approximately half of these immunization studies were conducted in pigs that were then exposed to an experimental challenge, but only a few compared their efficacy with commercially-available vaccines [15,23,42].…”
Section: Introductionmentioning
confidence: 99%